Comparison of the sorption capacity of basic, acid, direct and reactive dyes by compost in batch conditions. (15th September 2021) - Al-Zawahreh, Khaled; Barral, María Teresa; Al-Degs, Yahya; Paradelo, Remigio
Abstract: Research on biosorption of organic dyes is an important subject for the development of clean technologies for the treatment of textile wastewater. In this work, the process of sorption of four textile dyes of different natures, namely Basic Violet 10 (BV10), Acid Red 27 (AR27), Direct Blue 151 (DB151) and Reactive Violet 4 (RV4) onto two composts, pine bark compost and municipal solid waste compost, has been studied. For this, sorption kinetics and equilibrium sorption at different solution pH values (3.0–7.0) and salinity (0–1.0 M KCl) conditions have been assessed in batch experiments. Sorption rates were relatively slow for BV10, reaching equilibrium only after 24 h, and faster for the rest: around 5–6 h for RV4 and AR27 and 2 h for DB151. Kinetics of dye sorption followed a pseudo-first order model, except that of DB151, which was better described by a pseudo-second order model. The sequence of adsorption capacity for both composts was as follows: BV10 > DB151 > RV4 > AR27. In general, dye sorption at the equilibrium was adequately described by the Langmuir model, what allows to estimate maximum retention capacities for each dye by the composts. At the best removal conditions, pine bark compost presented maximum sorption capacities of 204 mg g −1 for BV10, 54 mg g −1 for DB151, 23 mg g −1 for RV4, and 4.1 mg g −1 for AR27, whereas municipal solid waste compost showed maximum sorption of 74 mg g −1 for DB151, 38 mg g −1 for RV4, 36 mg g −1 for BV10, and 1.6 mg g −1 for AR27. Sorption increased at acid pH in all cases, likely because of modification of charges of the dyes and higher electrostatic attraction, whereas increasing salinity also had a positive effect on sorption, attributed to a solute-aggregation mechanism in solution. In conclusion, organic waste-derived products, like composts, can be applied in the removal of colorants from wastewater, although they would be more effective for the removal of basic cationic dyes than other types, due to electrostatic interaction with mostly negatively-charged composts. Graphical abstract: Image 1 Highlights: Dye sorption on two composts has been studied at different pH and salinity conditions. Dye sorption capacity of both composts followed the sequence BV10 > DB151 > RV4 > AR27. Both composts increased their dye sorption capacity at acid pH and high salinity.